Pelanggaran Hak Cipta Drama Korea Melalui Platfrom Tiktok Dihubungkan dengan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Suryani, Ani (Universitas Medan Area, 2025)
This study aims to discuss the types of copyright infringement of video content on the TikTok platform and law enforcement for copyright infringement of video content on TikTok. The method used is normative law used to juxtapose laws and conceptual, using data collection in the form of secondary data. The results found that violations of property rights by sharing Korean dramas in the form of unauthorized video cuts through creators or copyright holders resulted in a decrease in ratings on legal streaming platforms and uploading Korean dramas that were watched by thousands of people without any royalties. Regulations to protect creators and copyright holders of their creations Law No. 28 of 2014, but in the complaint using a complaint offense so that the creator and copyright holder must directly report that there is a copyright infringement, as well as TikTok must first have a user report reporting that the content contains copyright infringement, this makes the freedom of irresponsible individuals increasingly free because the creators and copyright holders do not report it, so that copyright infringement committed on TikTok is considered commonplace.